Platform-dependent code generation for embedded real-time software - BaekGyu Kim; Phan, Linh T. X.; Sokolsky, Oleg; Insup Lee (2013 International Conference on Compilers, Architecture and Synthesis for Embedded Systems (CASES), 2013)
Code generation for embedded systems is challenging, since the generated code (e.g., C code) is expected to run on a heterogeneous set of target platforms with different characteristics, such as hardware/software architectures and programming interfaces. We propose a code generation framework that provides the flexibility to generate different source code that is executable on each target platform. In our framework, the platform-dependent characteristics of a target platform are explicitly specified by an Architectural Analysis Description Language (AADL) model and a code snippet repository. The AADL model captures hardware/software architectural aspects of the platform, such as periodic/aperiodic threads and their interactions with sensors and actuators. The code snippet repository contains platform-dependent code snippets that are categorized according to the functions required to implement the components of the AADL model. These two elements of the platform capability are then used by the code generation algorithm to generate platform-dependent code for the given platform. We demonstrate the applicability of our framework using a case study of code generation for two infusion pump systems.